Novel Corona Virus (COVID-19):Management of Maintenance Hemodialysis Patients - Baig, Zahid Farooq; Kashif, Nauman; Bokhari, Karamat Hussain (Pakistan Journal of Kidney Diseases, 2021)
Pandemic of novel corona virus (COVID-19) has evolved into a nightmare for nations both developed and underdeveloped. Patients of chronic kidney disease (CKD) on hemodialysis (HD) are at the increased risk of COVID-19 mainly due to older age, comorbid conditions, underlying immunecompromised state and hospital visits twice to thrice weekly for HD. This increases the risk both for the patients and health care workers for contracting the disease. This review details the different aspects of the COVID-19 infection as it relates to the dialysis staff and patients.